Obesity-resistance of UCP1-deficient mice associates with sustained FGF21 sensitivity in inguinal adipose tissue - Klein Hazebroek, Marlou; Keipert, Susanne (Frontiers in Endocrinology, 2022)
Metabolic diseases represent the major health burden of our modern society. With the need of novel therapeutic approaches, fibroblast growth factor 21 (FGF21) is a promising target, based on metabolic improvements upon FGF21 administration in mice and humans. Endogenous FGF21 serum levels, however, are increased during obesity-related diseases, suggesting the development of FGF21 resistance during obesity and thereby lowering FGF21 efficacy. In uncoupling protein 1 knockout (UCP1 KO) mice, however, elevated endogenous FGF21 levels mediate resistance against diet-induced obesity. Here, we show that after long-term high fat diet feeding (HFD), circulating FGF21 levels become similarly high in obese wildtype and obesity-resistant UCP1 KO mice, suggesting improved FGF21 sensitivity in UCP1 KO mice. To test this hypothesis, we injected FGF21 after long-term HFD and assessed the metabolic and molecular effects. The UCP1 KO mice lost weight directly upon FGF21 administration, whereas body weights of WT mice resisted weight loss in the initial phase of the treatment. The FGF21 treatment induced expression of liver Pck1, a typical FGF21-responsive gene, in both genotypes. In iWAT, FGF21-responsive genes were selectively induced in UCP1 KO mice, strongly associating FGF21-sensitivity in iWAT with healthy body weights. Thus, these data support the concept that FGF21-sensitivity in adipose tissue is key for metabolic improvements during obesogenic diets.